2015
DOI: 10.1021/acs.cgd.5b00657
|View full text |Cite
|
Sign up to set email alerts
|

CH···N Bonds and Dynamics in Isostructural Pyrimidine Polymorphs

Abstract: In the crystalline pyrimidine, the most basic building block of biochemical systems, the changes of entropy and enthalpy combine into a series of discrete structural transitions that have defied detection until now. The counterintuitive fully isostructural polymorphs of pyrimidine differ mainly by entropy, while the varied space occupied by molecules in partly isostructural polymorphs can be connected to the molecular dynamics, too. The interplay of thermodynamic and structural features affects the molecular i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 31 publications
0
38
0
Order By: Relevance
“…Furthermore, morphological cracking can appear at elevated temperatures due to anisotropic thermal expansion coefficients of semiconductors in different directions and/or between the semiconductors and dielectric layers. [30][31][32] The induced structural transition under different temperature is related to the rearrangement of molecules and changes in intermolecular interactions and has a significant impact on charge transport properties. [31][32][33] These grain-boundaries and thermal-crack defects provide the major trapping sites of charge carriers and cause device degradation under ambient air and moisture conditions.…”
Section: Doi: 101002/advs201900775mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, morphological cracking can appear at elevated temperatures due to anisotropic thermal expansion coefficients of semiconductors in different directions and/or between the semiconductors and dielectric layers. [30][31][32] The induced structural transition under different temperature is related to the rearrangement of molecules and changes in intermolecular interactions and has a significant impact on charge transport properties. [31][32][33] These grain-boundaries and thermal-crack defects provide the major trapping sites of charge carriers and cause device degradation under ambient air and moisture conditions.…”
Section: Doi: 101002/advs201900775mentioning
confidence: 99%
“…The fast solvent evaporation and quick depositing speed in the above methods also result in polycrystalline thick films with a high density of grain boundaries because of stochastic and spontaneous nucleation. Furthermore, morphological cracking can appear at elevated temperatures due to anisotropic thermal expansion coefficients of semiconductors in different directions and/or between the semiconductors and dielectric layers . The induced structural transition under different temperature is related to the rearrangement of molecules and changes in intermolecular interactions and has a significant impact on charge transport properties .…”
mentioning
confidence: 99%
“…Crystallographic data can be observed in the Supporting Information (Figure S1, Tables S1 and S2). The other structures used for this investigation can be found at CCDC under the following identification numbers 970351 13 ( 3I ), 970350 13 ( 3II ), 982074 12 ( 4I ), 1016402 12 ( 4II ), 170327 44 ( 5I ), 170330 44 ( 5II ), 201620 45 ( 6I ), 201621 45 ( 6II ), 1209196 46 ( 7I ), 174977 47 ( 7II ), 174978 47 ( 7IIIA ), 179359 48 ( 8I ), 179361 48 ( 8II ), 241464 49 ( 9I ), 241467 49 ( 9II ), 241469 49 ( 9III ), 1059291 50 ( 10I ), 1059297 50 ( 10II ), 1059309 50 ( 10III ), and 1059311 50 ( 10IV ).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the exchange of Me/Cl [ 4 ], Me/Br [ 5 ], as well as CH 2 /NH substitution [ 6 ], are also well known to result in isostructurality of the structures. Occurrence of 3D isostructurality in the presence of strong hydrogen bonds, namely N-H⋯N with the presence of weak C-H⋯N [ 7 ], C-H⋯F, C-H⋯π [ 8 ] interactions and π-π stacking was also reported. Bucar et al [ 9 ] showed that isostructural crystals can be obtained by an exchange of a > C=O to > C=S, but only if the studied oxygen/sulfur atom is not involved in hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%